The Problem of Distribution of Food Products and their Influence on the Decision of Purchasing in the Consumer a Case Study of Milk Products in the South, Algeria - Abdessamad, Boudi; Meriem, Azzouni; Abdenour, Bouzid; Redouane, Ait Kaci Azzou (International Journal of Business, Economics and Management, 2020)
The study aimed to find out and determine the effect of the distribution component and its channels on the purchasing decision of the Algerian consumer towards the Milk factory production in Bechar City, the south of Algeria. A sample consisting of 100 consumers was chosen from the study community, the searchers were used the questionnaire and the interview, SPSS statistical software was used, and after analyzing the data, the study showed that there is an effect of personal variables, gender, educational level, income in influencing the purchasing decision of the consumer, and there is also a relationship between the efficiency of the distribution channels and distributors in influencing the purchasing decision of the Algerian consumer, that was explained The effective role of the distribution channels contributed to raising consumer confidence and thus influencing its purchasing decisions.